Implementasi CSR (corporate social responsibility) di Koperasi Simpan Pinjam Maju Wijaya dalam meningkatkan perkembangan usaha mikro kecil dan menengah (UMKM) - Taniman, Sidhi Agustiana (Universitas Tarumanagara, 2017)
MSME is the hope of the Republic of Indonesia to continue to grow and develop, but this is not in line with the development of MSME, so many obstacles encountered, therefore the responsibility to empower MSME is not only a responsibility of the government, the responsibility of the company to participate in empowering MSME through corporate social responsibility activities to the community in general and MSME, especially in the form of CSR. Corporate Social Responsibility (CSR) is the way companies contribute or participate in providing benefits to the wrong perpetrators of society. The activities of corporate social responsibility (CSR) have been undertaken by companies based on the cooperative, Koperasi Simpan Pinjam Maju Wijaya in increasing the development of MSME through corporate social responsibility (CSR) activities. The method used is a descriptive qualitative method which is usually done for case study and data completion which is used using the interview technique, and taken from written sources from books, journals, and documentation related to Koperasi Simpan Pinjam Maju Wijaya in data management so that the result of it can be useful information. Conduct the activities of corporate social responsibility (CSR) to MSME conducted by Koperasi Simpan Pinjam Maju Wijaya through five key successes namely education, a discussion group forum, assistance, periodical visits, and periodic information for true CSR activity, can benefit MSME.